Providing a framework for the Myanmar government’s policies, programs and investments on climate-smart agriculture - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
In 2015, the Ministry of Agriculture, Livestock, and Irrigation (MOALI), together with CCAFS, developed the Myanmar Climate-Smart Agricultural Strategy (MCSAS) to guide the implementation of climate actions in Myanmar. To date, MCSAS has been referenced in at least 19 government and NGO programs, 4 policy documents, and 19 investment projects (worth approximately USD 1B investments). Furthermore, other CSA technologies and approaches were mainstreamed by various stakeholders as recommended in the MCSAS, such as the Climate-Smart Village(CSV) and climate-smart rice production.